If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -104 = 10 + -6w Solving -104 = 10 + -6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '6w' to each side of the equation. -104 + 6w = 10 + -6w + 6w Combine like terms: -6w + 6w = 0 -104 + 6w = 10 + 0 -104 + 6w = 10 Add '104' to each side of the equation. -104 + 104 + 6w = 10 + 104 Combine like terms: -104 + 104 = 0 0 + 6w = 10 + 104 6w = 10 + 104 Combine like terms: 10 + 104 = 114 6w = 114 Divide each side by '6'. w = 19 Simplifying w = 19
| 3(7m+5)+4(3m-8)=148 | | 4(2+5-24)=52-13 | | -6f-5+7f=21 | | 2y+5x-1=2x+4x-2 | | 2x(x-2)(x+1)=10 | | 2x+4-15=f[x] | | 2(4)+3(-1)= | | -5=3x-6 | | 4(8+3)-7=6a-21 | | 40=3t+14 | | x^3-2x^2+28x+56=0 | | 5x-20=2x+43 | | 13r+10=5-46 | | 140-3a=167 | | 2p-30=-4 | | d/12=7 | | -2-3-5+I-3I= | | 2p-30=4 | | 34-(-3)-(-7)= | | 8x-12=8x-17 | | 2a-5=2(a-3) | | 16n+67+4n+7-n=112 | | -(-3x+2)+2=-18 | | 8x+12=-2x-17 | | -18=n+1 | | 4d=148 | | 3+8y-16=-37 | | p-5-13p=10-11 | | 5-(-23)-39= | | 5n+8(1+7n)=-8 | | 2d=d+2 | | 8x=2(x-1+15) |